Jasmonate inhibits adventitious root initiation through repression of CKX1 and activation of RAP2.6L transcription factor in Arabidopsis. (30th July 2021) - Dob, Asma; Lakehal, Abdellah; Novak, Ondrej; Bellini, Catherine
Abstract : Genome-wide analysis in Arabidopsis revealed that light controls CK homeostasis during early stages of adventitious root initiation (ARI). CK and JA cooperatively inhibit ARI by inducing the transcription of the transcription factor RAP2.6L. Abstract: Adventitious rooting is a de novo organogenesis process that enables plants to propagate clonally and cope with environmental stresses. Adventitious root initiation (ARI) is controlled by interconnected transcriptional and hormonal networks, but there is little knowledge of the genetic and molecular programs orchestrating these networks. Thus, we have applied genome-wide transcriptome profiling to elucidate the transcriptional reprogramming events preceding ARI. These reprogramming events are associated with the down-regulation of cytokinin (CK) signaling and response genes, which could be triggers for ARI. Interestingly, we found that CK free base (iP, t Z, c Z, and DHZ) content declined during ARI, due to down-regulation of de novo CK biosynthesis and up-regulation of CK inactivation pathways. We also found that MYC2-dependent jasmonate (JA) signaling inhibits ARI by down-regulating the expression of the CYTOKININ OXIDASE/DEHYDROGENASE1 ( CKX1 ) gene. We also demonstrated that JA and CK synergistically activate expression of the transcription factor RELATED to APETALA2.6 LIKE (RAP2.6L), and constitutive expression of this transcription factor strongly inhibits ARI. Collectively, our findings reveal that previously unknown genetic interactions between JA and CK play key roles in ARI.